An opportunity cost Analysis of the Africa-One China Nexus, 2001-2016 - Ndzendze, Bhaso (My University, 2018)
Unlike in previous timeframes, between 2000 and 2016 no African state switched its recognition from the People’s Republic of China (PRC) to the Republic of China/Taiwan (ROC); but six switched in the opposite direction. Why was this the case? This thesis investigated the extent to which there was an opportunity cost for those African states (Liberia, Chad, Senegal, Gambia, Malawi, and São Tomé and Príncipe) in recognising the ROC as the “one China” over the People’s Republic of China in the period between 2001 and their respective year of switching, which in turn could explain the direction of the switches. In this thesis, opportunity cost, through time series and multiple comparative trade analyses, was operationalised as a relative economic loss (as measured through relative trade volumes, investment and aid) incurred that could have otherwise been avoided or compensated for by recognising the PRC over the ROC as the One China. The thesis found that in the timeframe studied, on average after three years, five out of six African countries (with the exception of São Tomé and Príncipe) that had previously recognised the ROC saw exponentially increased trade volumes with the PRC once they affected a switch in recognition from the ROC to the PRC (some saw this sooner). This is due to a number of factors; recognising the PRC is concomitant with entering into politically-enhanced bilateral economic relations at the behest of the PRC, at once a centralised state heavily involved in outward investments (thought the CDB and the EximBank) and the world’s second-largest economy. Those states which still recognise the ROC (presently only Burkina Faso and Swaziland) can be said to still do so in large part due to the fact that there has been a continual culling of allies and therefore a decrease in an “aid burden” on the comparatively economically stagnant ROC, since these six states have switched their recognition as well as being the recipients of “special attention” from the ROC government, not otherwise granted to the former allies. Thus while there can be said to be an opportunity cost, it can also be said to be bidirectional; without the one China problem, there would be, all other things being equal, no entities which would be highly motivated to dole out costly aid (at an opportunity cost) in the process of “dollar diplomacy”, especially since Taiwanese aid to its allies has been found in the thesis to increase, at least immediately, after an ally has switched towards the PRC. In other words, the enhanced trade and aid-giving are a means to an end rather than ends in themselves – were the one China issue resolved, there would be marginally fewer motivations for their continuation outside of commercial aims. This was seen, for example, during the 2008-2015 “diplomatic truce,” during which the PRC and the ROC experienced a thaw in their relations and temporarily seemed to be approaching rapprochement, as indicated by the signing of the PRC-ROC Economic Cooperation Framework Agreement, and at the same time did not attempt to lure each other’s allies with prospectively higher financial gains for so doing. In that sense, the opportunity cost is clearly there for both the PRC and the ROC as well as for African states as a result. This falls within, as well as practically vindicates, structural realist theorists such as Evera (1999) and Mearsheimer (2001) who assert that states, big and small, are rational agents (seeking to minimise costs and expand benefits), as well as relative gains-increasing actors.
Keywords: China--Relations; China--Economic conditions